If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 5) = 2 + 3(x + -8) Reorder the terms: x(5 + x) = 2 + 3(x + -8) (5 * x + x * x) = 2 + 3(x + -8) (5x + x2) = 2 + 3(x + -8) Reorder the terms: 5x + x2 = 2 + 3(-8 + x) 5x + x2 = 2 + (-8 * 3 + x * 3) 5x + x2 = 2 + (-24 + 3x) Combine like terms: 2 + -24 = -22 5x + x2 = -22 + 3x Solving 5x + x2 = -22 + 3x Solving for variable 'x'. Reorder the terms: 22 + 5x + -3x + x2 = -22 + 3x + 22 + -3x Combine like terms: 5x + -3x = 2x 22 + 2x + x2 = -22 + 3x + 22 + -3x Reorder the terms: 22 + 2x + x2 = -22 + 22 + 3x + -3x Combine like terms: -22 + 22 = 0 22 + 2x + x2 = 0 + 3x + -3x 22 + 2x + x2 = 3x + -3x Combine like terms: 3x + -3x = 0 22 + 2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-22' to each side of the equation. 22 + 2x + -22 + x2 = 0 + -22 Reorder the terms: 22 + -22 + 2x + x2 = 0 + -22 Combine like terms: 22 + -22 = 0 0 + 2x + x2 = 0 + -22 2x + x2 = 0 + -22 Combine like terms: 0 + -22 = -22 2x + x2 = -22 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x2 = -22 + 1 Reorder the terms: 1 + 2x + x2 = -22 + 1 Combine like terms: -22 + 1 = -21 1 + 2x + x2 = -21 Factor a perfect square on the left side: (x + 1)(x + 1) = -21 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 6+v-3=v+2 | | -4-2(-b-7)=6b-22 | | -7+9f=-1+10f | | -8(2x-5)+3x=4(x+7)-107 | | 6+x=6.1x | | -4-3(-b-7)=6b-22 | | -7-5v=-2(3v+6) | | 3x-2(x-1)=3(x+5) | | 6x+7-4x=8+7x-12 | | 4+3(5x+14)=39x-8 | | 6(3a+1)-30=3(2a+1) | | -65/5= | | 3(x+4)=-5 | | r^2-12r+33=8 | | 5x+10+4x-10=90 | | 6x-5/6=7/8 | | 3a-2a+2b-4+8a-b= | | .0009873= | | 5s^2-44s-9= | | x-1+10=3x-1 | | -24/4 | | |5-26|*(-3)/(-3) | | 18-3y=0 | | 16.87=1x+1.5x | | 6s=66 | | -17*3= | | 7.5y+1.6-2= | | 5n-6=5n-5 | | 13.1=-(k+6.2) | | 6t+5=5t | | 6(x+20)=168 | | 8*7(-6)= |